To solve the equation \( x^2 + 4x = 41 \) by completing the square, follow these steps:
-
Move the constant to the right side: \[ x^2 + 4x - 41 = 0 \quad \text{(but we can keep it in the original form for simplicity)} \]
-
Complete the square:
- Take half of the coefficient of \( x \) (which is 4), square it, and add it to both sides.
- Half of 4 is 2, and squaring it gives \( 2^2 = 4 \).
So, we update the equation: \[ x^2 + 4x + 4 = 41 + 4 \] Which simplifies to: \[ (x + 2)^2 = 45 \]
-
Take the square root of both sides: \[ x + 2 = \pm \sqrt{45} \]
-
Solve for \( x \): \[ x + 2 = \pm 3\sqrt{5} \] Therefore: \[ x = -2 \pm 3\sqrt{5} \]
So the solutions are: \[ x = -2 + 3\sqrt{5}, \quad x = -2 - 3\sqrt{5} \]
From the given options, the correct response is: x = −2 + 3√5, −2 − 3√5.